2021
DOI: 10.3389/fpsyt.2021.737357
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment or Attention-Deficit/Hyperactivity Disorder in Older Adults? A Cross Sectional Study

Abstract: Background: Attention-Deficit/Hyperactivity Disorder (ADHD) is a highly prevalent neurodevelopmental condition, which may be associated with life-enduring cognitive dysfunction. It has been hypothesized that age-related cognitive decline may overlap with preexisting deficits in older ADHD patients, leading to increased problems to manage everyday-life activities. This phenomenon may mimic neurodegenerative disorders, in particular Mild Cognitive Impairment (MCI). This cross-sectional study aims to assess cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…However, some limitations should be taken into account—namely the significant age differences between ADHD and MCI (mean age was 64 and 73.7, respectively), as well as sex differences with a greater proportion of females in the MCI group (72.4% in comparison with 52.5% in the ADHD group), which might play a role in the current findings. Mendonca et al (2021) reported in a cross-sectional study of older patients with ADHD ( n = 26), MCI ( n = 40) and controls ( n = 41), that ADHD individuals have poorer performance than controls in episodic memory and executive function. These findings were comparable between MCI and ADHD for all domains, which, for clinicians, may result in misdiagnosis ( Mendonca et al, 2021 ).…”
Section: Epidemiological Evidence For Attention-deficit Hyperactivity...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some limitations should be taken into account—namely the significant age differences between ADHD and MCI (mean age was 64 and 73.7, respectively), as well as sex differences with a greater proportion of females in the MCI group (72.4% in comparison with 52.5% in the ADHD group), which might play a role in the current findings. Mendonca et al (2021) reported in a cross-sectional study of older patients with ADHD ( n = 26), MCI ( n = 40) and controls ( n = 41), that ADHD individuals have poorer performance than controls in episodic memory and executive function. These findings were comparable between MCI and ADHD for all domains, which, for clinicians, may result in misdiagnosis ( Mendonca et al, 2021 ).…”
Section: Epidemiological Evidence For Attention-deficit Hyperactivity...mentioning
confidence: 99%
“… Mendonca et al (2021) reported in a cross-sectional study of older patients with ADHD ( n = 26), MCI ( n = 40) and controls ( n = 41), that ADHD individuals have poorer performance than controls in episodic memory and executive function. These findings were comparable between MCI and ADHD for all domains, which, for clinicians, may result in misdiagnosis ( Mendonca et al, 2021 ). Then again, the study by Leffa et al (2022) in which 212 cognitively healthy controls were followed up for 6 years, including baseline and longitudinal AD biomarkers assessment (e.g., amyloid-β PET, MRI, cognitive assessments etc.…”
Section: Epidemiological Evidence For Attention-deficit Hyperactivity...mentioning
confidence: 99%
“…In a cross‐sectional study involving 107 participants (41 controls, 40 MCI diagnoses and 26 ADHD diagnoses), participants with ADHD showed poorer performances than controls in episodic memory and executive function with large effect sizes 11 …”
Section: Adhd and Dementia: Similarities And Differencesmentioning
confidence: 99%
“…A recent investigation using the Swedish Medical Registry suggested a strong and significant association between ADHD in adulthood and later dementia (Du Rietz et al., 2021). It may be particularly important to understand the clinical implications of the relationship between these two conditions, especially considering their phenotypic and neuropsychological overlap (Mendonca et al., 2021).…”
Section: Charting the Developmental Coursementioning
confidence: 99%